Physicochemical, thermal, and functional properties of gari (fermented‐cassava product) enriched with cowpea hull at different stages of production. Issue 1 (21st March 2023) - Olapade, Gbemileke M.; Karim, Olayinka R.; Olawuyi, Ibukunoluwa F.
Abstract: Gari was produced using the traditional method and enriched with freshly produced cowpea hull in wet form to improve the nutritional composition. The objective of this study was to examine the effect of stages of inclusion of cowpea hull on some quality attributes of gari . Factorial design of two stages of inclusion (before and after fermentation) with four levels (0%, 3%, 5% and 7%) of cowpea hull treatments and standard methods were used to analyze the gari . Stages of inclusion of cowpea hull had a significant ( p < 0.05) effects on lightness ( L *) which reduced as percentage of cowpea hull increased while redness ( a *), yellowness ( b *) and change in colour increased as cowpea hull increased. Fourier transform infrared spectroscopy shows a diverse functional group with more than five peaks in the graph. Thermal properties reduced as percentage of cowpea hull increased in the fermented cowpea hulls samples and increased in unfermented which was evident in the pasting properties (1275–2143 RVU, 93–271 RVU, 5.92–6.97 min and 51.70–95.06°C for peak viscosity, breakdown, peak time and temperature), respectively. Enrichment of gari using 5% cowpea hull fermented with the cassava mash is therefore recommended. Abstract : The stages of inclusion of cowpea hull had a significant effect on the enriched gari. Fourier transform infrared spectroscopy shows diverse functional groups. Thermal properties reduced as the percentage of cowpea hull increased in the fermented cowpea hulls samples and increased in unfermented. Enrichment of gari using 5% cowpea hull had the best physicochemical, thermal and functional properties.